2018
DOI: 10.1016/j.ijnurstu.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Challenges adhering to a medication regimen following first-time percutaneous coronary intervention: A patient perspective

Abstract: Patients undergoing first-time percutaneous coronary intervention face multiple, interacting challenges in trying to adhere to prescribed medications following discharge. This study highlights the need for a more structured follow-up care in order to improve medication adherence and to maximise their self-care abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 46 publications
(59 reference statements)
5
47
0
Order By: Relevance
“…47 Several studies support the notion that patients often experience a reluctance in doctors or other healthcare professionals to discuss the risk of adverse effects. [48][49][50][51] In our study, a feeling of uncertainty, as opposed to security, was connected to a lack of information. Participants were not asked about the specific information they had been given or what they did not have, but they nonetheless mentioned missing information or not knowing enough about their need for drugs, as in a recent study of patients who had undergone percutaneous coronary interventions (PCI) in Norway.…”
Section: Relationships and Interactions With Cliniciansmentioning
confidence: 48%
See 1 more Smart Citation
“…47 Several studies support the notion that patients often experience a reluctance in doctors or other healthcare professionals to discuss the risk of adverse effects. [48][49][50][51] In our study, a feeling of uncertainty, as opposed to security, was connected to a lack of information. Participants were not asked about the specific information they had been given or what they did not have, but they nonetheless mentioned missing information or not knowing enough about their need for drugs, as in a recent study of patients who had undergone percutaneous coronary interventions (PCI) in Norway.…”
Section: Relationships and Interactions With Cliniciansmentioning
confidence: 48%
“…Participants were not asked about the specific information they had been given or what they did not have, but they nonetheless mentioned missing information or not knowing enough about their need for drugs, as in a recent study of patients who had undergone percutaneous coronary interventions (PCI) in Norway. 48 Several other studies have also mentioned a lack of information and, perhaps more importantly, have found that patients need very different types of information, adapted to their own personal situations, and that the kind of information needed varies over time. 39,49,50,[52][53][54] The findings in our study associated with the active experience of learning to live with medicines, and taking or feeling responsibility, reflect how medicines are included in the everyday life of patients.…”
Section: Relationships and Interactions With Cliniciansmentioning
confidence: 99%
“…However, the failure to make lifestyle changes and misunderstandings regarding CHD and a cardioprotective lifestyle are common (Perk et al, ; Wiecek et al, ). The predominance of non‐adherence regarding medication (Ibanez et al, ; Pettersen et al, ) and a healthy lifestyle (Booth et al, ; Ibanez et al, ) is estimated to range from 30% to 60% among patients with CHD after PCI (Perk et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, unintentional non‐adherence refers to a patient's lack of capacity or cognitive resources, which can lead to non‐adherence. (Molloy et al, ; Pettersen et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation